Association of obstructive sleep apnea on surgically treated cleft anomalies - Kamath K., Madhava; Philip, Prijo; Shetty, Vikram; Venkataram, Rajesh; B. H., Giridhar (International Journal of Contemporary Pediatrics, 2016)
Background: Palatoplasty is frequently employed to correct the many anatomical and physiological effects of cleft disorders in children, including Obstructive Sleep Apnea (OSA). It is as yet unclear, whether Sleep Disordered Breathing (SDB) and OSA are encountered post palatoplasty. This study attempts to analyze the occurrence, if any, of the same. Methods: The study is a retrospective analysis, involving patients who had undergone palatoplasty. Patients were subjected to overnight Polysomnography (PSG), and data pertaining to Apnea Hypopnea Index (AHI), Desaturation Index (DI) and Periodic Limb Movements (PLMS) were recorded. Results: Of the 21 patients evaluated for post palatoplasty OSA, eleven patients were found to have mild OSA (52.3%), and four patients had moderate OSA (19.04%). Of the patients with mild OSA, five patients had complaints of postoperative snoring (45.4%). Conclusions: A sizeable risk of post palatoplasty OSA does exist, and the incidence of postoperative OSA may be higher than previously noted. However, further studies are warranted, in this regard.